PEMANFAATAN AIR KELAPA UNTUK MENINGKATKAN PERTUMBUHAN AKAR STEK TUNAS AKSILAR Andrographis paniculata Nees - Retno Prihatini (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
The research has been conducted to find out the best concentration of coconut water in the induction of roots of cuttings axillary buds Andrographis paniculata Nees. This research was conducted in Plant Physilogy of Division, Department of Biology, Faculty of Math and Natural Science, AndalasUniversity, for 12 weeks. The research used Completely Randomized Design. The material used was axillary buds A. paniculata with nodal number 3. treated for 30 minutes in coconut water 10, 15 and 20% and aquadest as a controle each with 6 replications. Observations were done on live percentage, root length, root numerous and cuttings height after 12 weeks planting. The results showed that the concentration 10 to 15% of coconut water was able with significant to induce the root growth of cutting axillary buds A. Paniculat. The concentration 15% of coconut water was the best in inducing cutting height growth, each with an average root length is 8.2 cm and the average number of roots that formed is 16, 0 and the average cutting height is 22.7 cm. There was an increase of average of cuttings height growth by 86% which was supported by the average increase of root length and root number of 105.0% and 280.9% on the occasion of cuttings of axillary buds in coconut water concentration 15%.